Mental health and organizational quality of primary healthcare services in Brazil - Sanine, Patricia Rodrigues [UNESP]; Silva, Letícia Isabel Ferreira [UNESP] (My University, 2021)
The study aimed to assess the quality of care for persons with mental health distress in primary healthcare services in Brazil and the association with organizational structure variables. This evaluative study used data from the Brazilian National Program to Improve Acess and Quality in Primary Care (PMAQ-AB), collected in 2018. The study excluded teams that reported not performing this type of care. The sum of the 13 selected mental health indicators produced a score that was classified in three groups of quality: G1 (0 to 5 points – lower quality), G2 (6 to 9 points – medium quality), and G3 (10 to 13 points – higher quality), and the results were associated with nine organizational context variables favoring the teams’ permanence in the respective quality groups. The study evaluated 36,384 teams, located in 5,026 municipalities (counties). The score ranged from 1 to 13 points (G1 = 9.7%; G2 = 25.1%; G3 = 65.2%). Having an environment favorable to dispensing medicines and privacy during patient consultations; existence of a medical specialist, psychologist, and pharmacist; inter-consultation with the Expanded Family Health Care Centers (NASF) and Centers for Psychosocial Care (CAPS); and weekly or biweekly team meetings, were more frequent in the teams with higher quality (p < 0.001). In conclusion, structural conditions related to infrastructure and availability of healthcare workers, as well as inter-consultation and spaces for reflection to discuss the (re)organization of work processes in care for patients with mental health distress are factors that influence the quality of care, requiring attention, especially given recent political setbacks.
Saúde mental e a qualidade organizacional dos serviços de atenção primária no Brasil
Keywords: Health Evaluation; Health Management; Health Services; Mental Health; Primary Health Care